2018
DOI: 10.1001/jamainternmed.2017.7978
|View full text |Cite
|
Sign up to set email alerts
|

Lactation Duration and Progression to Diabetes in Women Across the Childbearing Years

Abstract: IMPORTANCE Lactation duration has shown weak protective associations with incident diabetes (3%-15% lower incidence per year of lactation) in older women based solely on self-report of diabetes, studies initiated beyond the reproductive period are vulnerable to unmeasured confounding or reverse causation from antecedent biochemical risk status, perinatal outcomes, and behaviors across the childbearing years.OBJECTIVE To evaluate the association between lactation and progression to diabetes using biochemical te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
2
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 58 publications
2
119
2
5
Order By: Relevance
“…reverse causality), which predisposes to both short BF duration and metabolic disease. If so, this could explain both the positive association between BF and later good metabolic health found in previous observational studies, and also the lack of such an effect in the PROBIT study . By exploring development in metabolic health parameters in different BF‐duration groups, we aimed to disentangle effects of BF on long‐term maternal metabolic health from effects of pre‐pregnant health on BF duration and long‐term metabolic health.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…reverse causality), which predisposes to both short BF duration and metabolic disease. If so, this could explain both the positive association between BF and later good metabolic health found in previous observational studies, and also the lack of such an effect in the PROBIT study . By exploring development in metabolic health parameters in different BF‐duration groups, we aimed to disentangle effects of BF on long‐term maternal metabolic health from effects of pre‐pregnant health on BF duration and long‐term metabolic health.…”
Section: Introductionmentioning
confidence: 97%
“…Previous large observational studies report positive effects of BF on maternal metabolic health, such as reduced risk of diabetes, hypertension, hyperlipidaemia, and cardiovascular disease later in life . Some studies have found that women who breastfeed lose weight faster postpartum and that BF duration is inversely correlated with body mass index (BMI) and waist circumference (WCF) .…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, they should promote breastfeeding. There is strong evidence from a 30‐year prospective cohort study that lactation duration is associated with a lower incidence of diabetes in women with and without GDM …”
Section: Implications For the Obstetricianmentioning
confidence: 99%
“…There is strong evidence from a 30-year prospective cohort study that lactation duration is associated with a lower incidence of diabetes in women with and without GDM. 42 Secondly, obstetricians should communicate to women and their primary care providers that the rate of progression to T2DM is highest within 3-6 years of GDM. 8,9 The NICE 2015 guideline for diabetes in pregnancy recommends that women with GDM are all offered diet and lifestyle advice and a fasting blood glucose check between 6 and 13 weeks postpartum, followed by annual HbA1c screening thereafter.…”
Section: Women With Gestational Diabetes Mellitusmentioning
confidence: 99%
“…3,4 Several studies have found a graded association between lactation duration and the risk of diabetes. [5][6][7][8][9][10][11] However, selfreported diagnoses of diabetes were used in some of these studies rather than the lab measurement to define the major outcome. 5,9 Moreover, few studies have assessed the association of lactation intensity and duration with postpartum diabetes risk among women with GDM, and their results remain inconsistent because of the relatively small sample sizes of women with GDM, few cases of type 2 diabetes, 10,11 and short follow-up time.…”
Section: Introductionmentioning
confidence: 99%